Pemanfaatan Aplikasi Mendeley Desktop dalam Mengelola Referensi Tugas Akhir Mahasiswa - Reni Suci Wahyuni; Dani Rizana (Beru'-beru': Jurnal Pengabdian kepada Masyarakat, 2023)
Students will be presented with various types of assignments, both in the form of written work and scientific work or thesis during the process of studying at university. One important part of scientific work is references. The use of references aims to provide sources of information used in writing scientific papers. The use of references is important in scientific work because it provides legitimacy and reliability to the scientific work created. The main aim of this activity is to provide students with skills in managing bibliography with the aim of creating citations and managing libraries automatically, so as to reduce the potential for acts of plagiarism which are often committed by students. The implementation method uses the experiential learning method. The results of this community service activity can help students overcome various challenges related to research literature, including reference or bibliography management, literature analysis, and team collaboration. Using the Mendeley application can make a positive contribution to the quality and efficiency of students' final assignment research, as well as enriching their experience in the academic world.